Sustainable Islamic Lifestyle through Planting Ornamental Plants and Medicinal Plants: P5-PPRA Project - Saiful Bahri; Suci Siti Nurbarkah; Wiwit Kurniati Rohmah (Mozaic : Islam Nusantara, 2025)
Islamic education plays a significant role in shaping students who are faithful, knowledgeable, and morally upright. As formal educational institutions, madrasahs are expected not only to achieve intellectual excellence but also to cultivate social, spiritual, and ecological awareness among students. However, the integration of environmental education with religious values in madrasahs remains limited. This study aims to describe the implementation of the P5-PPRA Project towards an Eco Madrasah through the Sustainable Lifestyle theme, specifically through the planting and maintenance of ornamental and medicinal plants at MI Darul Ulum Bantaran, and to analyze the ecological and religious character values developed among students. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation, and analyzed interactively following the Miles and Huberman model. The findings indicate that these activities successfully foster responsibility, cooperation, discipline, environmental awareness, independence, spiritual consciousness, and high student enthusiasm. Furthermore, the integration of Islamic ecotheology and fiqh al-bi’ah principles ensures that the learning process is contextual, practical, and effective in developing students’ eco-spiritual character. In addition, the successful implementation of these activities provides opportunities for developing entrepreneurial initiatives based on ornamental and medicinal plants, allowing students to generate beneficial products while enhancing their ecological and religious literacy. The P5-PPRA Project thus demonstrates an effective model for establishing Eco Madrasahs oriented towards environmental sustainability and the cultivation of religious values.